Ex-vivo Expansion of Adult Human Pancreatic Beta-Cells (The Review of Diabetic Studies, 2023)
Ex-vivo generation of human insulin-producing cells is considered a promising approach to providing an abundant source of cells for beta-cell replacement therapy in diabetes. Expansion of adult beta-cells from the limited number of islet donors is an attractive prospect. However, while evidence supports the replicative capacity of both rodent and human beta-cells in vivo, attempts at expanding these cells in tissue culture result in loss of beta-cell phenotype, making it difficult to track their fate during continuous propagation and raising doubts about their therapeutic potential. Recent lineage-tracing studies demonstrate the ability of human beta-cells to survive and replicate to a significant degree in vitro. Beta-cell delamination out of the normal epithelial structure, a process that results in dedifferentiation, seems to be required for significant in-vitro proliferation. Therefore, ways must be found of inducing redifferentiation of the expanded cells ex vivo, or of restoring their function upon transplantation. Elucidation of the signaling pathways altered during beta-cell adaptation to growth in culture may provide clues to cell redifferentiation. In a recent study, we found that human beta-cell dedifferentiation and entrance into the cell cycle in vitro correlated with activation of the Notch pathway and downregulation of the cell cycle inhibitor p57. Inhibition of the Notch downstream target HES1 using short hairpin RNA reduced beta-cell dedifferentiation and replication, suggesting a potential target for inducing cell redifferentiation following expansion in culture. This review critically discusses the potential for using ex-vivo beta-cell replication and redifferentiation in cell replacement therapy in diabetes.